The Validity of the Vibrations, Waves, and Sounds - Related Guided Inquiry Learning Material Assisted by Google Sites - Astin Lukum; Tirtawaty Abdjul; I Made Hermanto (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the validity of the vibration, waves, and sounds – related guided inquiry learning material assisted by Google sites. This type of research is quantitative research with a descriptive approach that is focused on the validation test process through expert validation tests. The instrument used in this research is the expert validation sheet. The learning material validated in this study include lesson plans, student worksheets, teaching materials, learning media and learning outcomes tests. The results of lesson plans validation by experts obtained an average score of 3.3 (valid). For the validation of the student worksheets, the average score is 3.1 (valid). The validation of teaching materials obtained an average score of 3.4 (valid). The validation of learning media obtained an average score of 3.4 (valid). And the learning outcomes test obtained validation results with an average score of 3.2 (valid). From these results, the overall average value of the validation of learning tools is 3.3 and is included in the valid category. So it can be concluded that the guided inquiry learning material assisted by Google sites on the material of vibration, waves, and sound developed is feasible to be used in the learning process.